Unilateral plantar erythema nodosum in sarcoidosis - Hueber, Axel; Schett, Georg; Manger, Bernhard (Arthritis and Rheumatology, 2017)
A 32-year old male Caucasian patient presented with mild exertional dyspnea, pain and swelling of both ankles, and general malaise. On examination symmetrical arthritis of both ankles and a vivid nodular erythema with slight pain on pressure was detected on the sole of the right foot (A). A therapy with ibuprofen had not led to any improvement of symptoms. This article is protected by copyright. All rights reserved.
EVALuna2:13347